2015
DOI: 10.22610/jebs.v7i1(j).561
|View full text |Cite
|
Sign up to set email alerts
|

Online Store Service Convenience, Customer Satisfaction and Behavioural Intentions: A Focus on Utilitarian Oriented Shoppers

Abstract: The paper investigates, using transaction cost theory, the concept of service convenience and its influence on utilitarian customer satisfaction and behavioural intentions to repurchase from an online store. Data used in the analysis was collected from utilitarian oriented online shoppers from Gauteng, South Africa using a structured questionnaire. According to the findings search, evaluation, order and possession convenience were identified as unique,reliable and valid dimensions of service convenience in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
4
23
0
1
Order By: Relevance
“…Similarly, Jiang, Yang and Jun (2013) found that online shoppers have a favorable perception of online shopping in Hong Kong. This finding is also supported by the study conducted in South Africa by Mpinganjira (2015) who found that online shoppers have a favorable perception of search and possession convenience. This study found that demographic variables (gender, age, education, occupation and income) do not have a significant relationship with shoppers' perception of retail convenience in online shopping.…”
Section: Discussion Of Findingssupporting
confidence: 76%
“…Similarly, Jiang, Yang and Jun (2013) found that online shoppers have a favorable perception of online shopping in Hong Kong. This finding is also supported by the study conducted in South Africa by Mpinganjira (2015) who found that online shoppers have a favorable perception of search and possession convenience. This study found that demographic variables (gender, age, education, occupation and income) do not have a significant relationship with shoppers' perception of retail convenience in online shopping.…”
Section: Discussion Of Findingssupporting
confidence: 76%
“…They found that service convenience was a significant antecedent of satisfaction with Internet use [22]. Mpinganjira [21] identified service convenience dimensions in the context of online stores and verified that an online store's service convenience influenced service satisfaction with a sample consisting of 127 online consumers: 88.8% were aged between 18 and 49, while 10.2% were more than 50 years old.…”
Section: Customer Satisfactionmentioning
confidence: 92%
“…Convenience products should not require too much effort and time to compare and purchase [30] and pose low risks to customers [31]. Since service convenience reduces customers' time and energy expenditure [15], a number of scholars have examined the convenience in various fields, such as online stores [21], art museums [32], and commercial banks [33]. In the tourism field, although Chang et al [34] addressed convenience as a key factor driving customer satisfaction in the restaurant industry, identifying crucial factors of online customer convenience still remains an important issue for the tourism industry in the circumstance that the number of traditional agents is decreasing due to technological advances.…”
Section: Service Conveniencementioning
confidence: 99%
See 1 more Smart Citation
“…Bu bilgiye dayanarak firmalar seçtikleri pazarlama stratejisi ve konumlandırma tercihine uygun, hazcı tüketim alışveriş ortamı veya faydacı tüketim alışveriş ortamı yaratabilmektedir(Scarpi vd., 2014). Çevrimiçi perakende sektöründeki firmalar rekabetçi kalabilmek ve müşteri değerini artırabilmek için farklı ve etkili yollar arayışı içine girmektedirler(Mpinganjira, 2015). Özellikle perakende sektöründeki rekabet artışı, pazarlamacıları farklı mağaza düzenleri oluşturmaya motive etmektedir.…”
unclassified